2021
DOI: 10.1155/2021/5426595
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Mind and Body Exercises for Neck Pain: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background. Neck pain is common and can have a significant impact on patients’ physical functionality, mobility, and quality of life (QOL). In clinical practice, traditional Chinese mind and body exercise (TCMBE) is a combination of different types of exercise based on traditional Chinese medicine, including qigong, tai chi, the 12-words-for-life-nurturing exercise, and so on, and many studies have found that it is safe and effective at helping patients with neck pain. Objective. The aim of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…The previous systematic review reported that there was insufficient evidence to support the clinical use of TCEs in improving pain intensity and enhancing functional mobility and quality of life in individuals with neck pain (Xie et al, 2021). However, there were only six studies of TCEs for neck pain published in English.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous systematic review reported that there was insufficient evidence to support the clinical use of TCEs in improving pain intensity and enhancing functional mobility and quality of life in individuals with neck pain (Xie et al, 2021). However, there were only six studies of TCEs for neck pain published in English.…”
Section: Discussionmentioning
confidence: 99%
“…In China, traditional Chinese exercises (TCEs) are widely used in the treatment of neck pain and associated conditions, which include Tai Chi, Qigong, Yijinjing, Baduanjin, Liuzijue, and Five-animal exercises (Xie et al, 2021). TCEs take both body and mind into account, emphasize the coordination and unification of breathing and body movements under the guidance of consciousness, and exercise the muscles and joints of the whole body (Lan et al, 2013;Solloway et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Diagnostic and Efficacy Standard of TCM Disease (34), a total of 10 studies (39,41,42,(44)(45)(46)(47)(48)(49)(50) reported the percentage of total efficacy. The results showed that the treatment group was better than the control group [RR = 1.17, 95% CI (1.10, 1.25), P < 0.001] in the Heterogeneity test (P = 0.50, I 2 = 0%, see Figure 8).…”
Section: General Efficiencymentioning
confidence: 99%
“…As a result of the above, several initiatives have been developed to reduce burnout in healthcare professionals, including structural interventions (e.g., shortened attending rotation length and various modifications to clinical work processes) and individual-focused interventions (e.g., stress management and self-care training or communication skills training), with encouraging results ( Luberto et al, 2017 ). Among the wide range of strategies available, brief mindfulness-based programs have gained ground in the past years due to their relatively reduced costs, moderate efficacy, healthcare acceptability, and their ability to enhance job performance ( Gracia Gozalo et al, 2018 ; Pérez-Aranda et al, 2019 ; Xie et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%